1998
DOI: 10.1063/1.477341
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic-field effects on the recombination fluorescence of anthracene cation and perfluorocarbon anions

Abstract: Articles you may be interested inMagnetic field effects in singlet-polaron quenching in molecularly doped fluorescence organic light-emitting diodes J. Appl. Phys. 116, 064308 (2014); 10.1063/1.4892625Hyperfine interaction mechanism of magnetic field effects in sequential fluorophore and exciplex fluorescence D 1 ( 2 B 2g )→D 0 ( 2 A u ) fluorescence from the matrix-isolated perylene cation following laser excitation into the D 5 ( 2 B 3g ) and D 2 ( 2 B 3g ) electronic states Yield determination of OH (v=0,1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…It is appropriate to acknowledge that K. M. Salikhov and colleagues [2,3] demonstrated that systems with equivalent nuclei, such as radical anion of hexafluorobenzene, can in principle produce observable lines in nonzero fields -multiples of the single HFC constant AHF. Although much weaker than the ubiquitous zero-field line, these "satellite" lines were then indeed observed experimentally [4,5], and even richer spectra were reported later [6]. The uniqueness of systems with equivalent nuclei lies in a very regular energy level layout governed by just one parameter AHv, so that the crossings for them also occur at regular, well-defined places and thus lend themselves to experimental observation.…”
Section: Introductionmentioning
confidence: 91%
“…It is appropriate to acknowledge that K. M. Salikhov and colleagues [2,3] demonstrated that systems with equivalent nuclei, such as radical anion of hexafluorobenzene, can in principle produce observable lines in nonzero fields -multiples of the single HFC constant AHF. Although much weaker than the ubiquitous zero-field line, these "satellite" lines were then indeed observed experimentally [4,5], and even richer spectra were reported later [6]. The uniqueness of systems with equivalent nuclei lies in a very regular energy level layout governed by just one parameter AHv, so that the crossings for them also occur at regular, well-defined places and thus lend themselves to experimental observation.…”
Section: Introductionmentioning
confidence: 91%
“…al, 1985) that specifically explored level crossings in nonzero fields for radical pairs with equivalent nuclei in only one pair partner, and gave explicit expression for their position determined by the hyperfine coupling (HFC) constant. Such lines were later indeed experimentally observed in several systems by two teams 35 (Stass et al, 1995b;Saik et al, 1995;Grigoryants et al, 1998;Kalneus et al, 2006a). Furthermore, in a subsequent paper (Tadjikov et al, 1996) it was suggested and demonstrated in numerical simulations for several systems of simple structure, and confirmed in a proof-of-principle experiment, that hyperfine structure of the second pair partner may be revealed at the level crossing lines.…”
mentioning
confidence: 66%
“…Although nuclei with spins 3 2 and higher, like 35,37 Cl ( 3 2 ) (Bagryansky et al, 1998), 27 Al ( 5 2 ), 69,71 Ga( 3 2 ), 113,115 In ( 92 ) (Sergey et al, 2012), 73 Ge( 92 ) (Shokhirev et al, 1991;Borovkov et al, 2003) occasionally occur in magnetic field effect experiments, so far the only resolved lines in multiple fields of Eq. (7) have been reported for systems containing sets of equivalent spin-1 2 nuclei, either protons or fluorines (Stass et al, 1995b;Saik et al, 1995;Grigoryants et al, 1998;Kalneus et al, 2006a). The best results making them promising for such applications were obtained 185 for radical anions of either hexafluorobenzene (six fluorines with a=13.7 mT) or octafluorocyclobutane (eight fluorines with a=15.1 mT) paired with a narrow partner radical cation.…”
Section: Even Number Of Equivalent Spin-1 2 Nuclei To Drive Spin Evolmentioning
confidence: 99%
“…In our picture it appears as arising of anticrossings at the zero field that spreads and counteracts the active crossings originally present there, additionally washing away the well-defined partitioning into state subspaces with pronounced state interference. Another place where the crossing vs. anticrossing discussion is very relevant is the so-called J resonance in radical pairs (Hamilton et al, 1989;Shkrob et al, 1991) or linked donor-acceptor dyads (Weller et al, 1984;Ito et al, 2003;Wakasa et al, 2015;Steiner et al, 2018), where exchange coupling between the two partners shifts the triplet electron spin manifold relative to the singlet, and at a certain magnetic field the singlet term crosses with one of the triplet sublevels. In many cases these crossings turn into an anticrossing due to additional weaker interactions, such as HFC with magnetic nuclei, but traditionally the situation is often still referred to as "ST − crossing", even though the technical discussion clearly identifies it as anticrossing.…”
Section: Introducing Nuclei Into the Driving Partner: Crossings Vs Anmentioning
confidence: 99%